2022
DOI: 10.3389/fcell.2021.801959
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lactate Metabolism-Related Gene Signature for Predicting Clinical Outcome and Tumor Microenvironment in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the main subtype of primary liver cancer with high malignancy and poor prognosis. Metabolic reprogramming is a hallmark of cancer and has great importance on the tumor microenvironment (TME). As an abundant metabolite, lactate plays a crucial role in cancer progression and the immunosuppressive TME. Nonetheless, the potential roles of lactate in HCC remain unclear. In this study, we downloaded transcriptomic data of HCC patients with corresponding clinical information from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…They showed a low mutation rate but strong correlation with immune cells in our results, which indicated their tumorigenic roles were not as an oncogene but affected the immune microenvironment. The prognosis value of lactate was reported in hepatocellular carcinoma recently [ 26 ], while LUAD was not mentioned. In our study, multiple clustering analysis distinguished top genes into two groups according to survival.…”
Section: Discussionmentioning
confidence: 99%
“…They showed a low mutation rate but strong correlation with immune cells in our results, which indicated their tumorigenic roles were not as an oncogene but affected the immune microenvironment. The prognosis value of lactate was reported in hepatocellular carcinoma recently [ 26 ], while LUAD was not mentioned. In our study, multiple clustering analysis distinguished top genes into two groups according to survival.…”
Section: Discussionmentioning
confidence: 99%
“…Researches about PET117 indicated that it is necessary for Cox15 oligomerization and function in mitochondrial respiratory ( 51 ), which means it might related to cell energy metabolism. There was a bioinformatic analyse identified PET117 as hub gene related to TME and prognosis of hepatocellular Carcinoma ( 52 ). The TAF9(TATA-binding protein) was also identified as a prognostic gene in a DNA-repair-related gene model for esophageal cance ( 53 ), our results showed that MHPS was also associated DDR, which suggested that TAF9 might involved in tumor processes, and discovered as a potential target in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…NDUFB9 and NDUFB10 were associated with mitochondrial respiratory chain complex I assembly. Li et al (2021) found that deletion of NDUFB9 promoted proliferation and invasion of metastatic breast cancer cells via Akt/mTOR/p70S6K axis. Hebert-Chatelain et al (2012) revealed that activation of Src kinase could inhibit NDUFB10 phosphorylation and decrease mitochondrial respiration to increase aerobic glycolysis.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous researches revealed that aberrant expression of PUS1 was closely linked to lactic acidosis and mitochondrial myopathy ( Knispel et al, 2021 ). Li et al (2021) suggested that elevated levels of PUS1 were intimately connected with poor prognosis of hepatocellular. NDUFB9 and NDUFB10 were associated with mitochondrial respiratory chain complex I assembly.…”
Section: Discussionmentioning
confidence: 99%